2002
DOI: 10.1111/j.1748-0361.2002.tb00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Diets Consumed by Older Rural Adults

Abstract: Older adults residing in rural communities are at risk for low dietary quality because of a variety of social, physical and environmental circumstances. Minority elders are at additional risk because of poorer health status and lower socioeconomic status. This study evaluated the food group intake of 130 older (>70 years) African American (34%), European American (36%), and Native American (30%) residents of two rural communities in central North Carolina. An interviewer-administered food frequency questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
(31 reference statements)
2
21
0
Order By: Relevance
“…Older adults in rural communities are at risk for inferior dietary quality because of a variety of social, physical, and environmental circumstances (5). Inherently, older adults in rural India are at greater risk of nutritional deficiencies than younger adults due to physiological changes with aging, financial and social constraints, and functional decline (6).…”
Section: Introductionmentioning
confidence: 99%
“…Older adults in rural communities are at risk for inferior dietary quality because of a variety of social, physical, and environmental circumstances (5). Inherently, older adults in rural India are at greater risk of nutritional deficiencies than younger adults due to physiological changes with aging, financial and social constraints, and functional decline (6).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the food group intake for the older adults surveyed was lower than recommended levels [4,5,6,7,12]. When MyPyramid was released in 2005, one of the changes made was to redefine serving size.…”
Section: Resultsmentioning
confidence: 83%
“…Previous reports of food group intake have shown older adults tend to consume fewer than the recommended servings for each of the food groups [4,5,6]. Older adults are most likely to meet the recommended intake of fruit [5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to gender, studies show instances of both Black women or Black men having inadequate diets (Bowman 2007;Cohen, Ralston et al 1998;Davis et al 2000;Prothro and Rosenbloom 1999;Sharkey and Schoenberg 2002;Tangney et al 2001;Vitolins et al 2002). However, some research has shown that African American women may have lower dietary quality (Bowman, 2007;Prothro and Rosenbloom 1999;Sharkey and Schoenberg 2002), even with income controlled.…”
Section: The Influence Of Individual Factorsmentioning
confidence: 91%